2022
DOI: 10.48550/arxiv.2201.05054
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Mapping SYK to the Sky

Sabrina Pasterski,
Herman Verlinde

Abstract: The infrared behavior of gravity in 4D asymptotically flat spacetime exhibits a rich set of symmetries. This has led to a proposed holographic duality between the gravitational S-matrix and a dual field theory living on the celestial sphere. Most of our current understanding of the dictionary relies on knowledge of the 4D bulk. As such, identifying intrinsic 2D models that capture the correct symmetries and soft dynamics of 4D gravity is an active area of interest. Here we propose that a 2D generalization of S… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(10 citation statements)
references
References 54 publications
0
10
0
Order By: Relevance
“…Recent findings of different correlation functions in these theories [65,66] As mentioned before, in order to reproduce flatspace scattering, as in Celestial CFTs, Carroll CFTs need an infinite number of primary fields with complex scaling dimension. Moreover, the celestial CFT enjoys a much larger symmetry [20][21][22][23][24][25][26][27][28][29][30]32] than the extended BMS 4 algebra and these additional symmetries play a central role in holographic computation of scattering amplitudes. We would ideally like to construct an explicit example of such a theory to provide a concrete proposal between a gravitational theory in asymptotically flat spacetimes and a Carroll CFT with additional symmetries living on its null boundary.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Recent findings of different correlation functions in these theories [65,66] As mentioned before, in order to reproduce flatspace scattering, as in Celestial CFTs, Carroll CFTs need an infinite number of primary fields with complex scaling dimension. Moreover, the celestial CFT enjoys a much larger symmetry [20][21][22][23][24][25][26][27][28][29][30]32] than the extended BMS 4 algebra and these additional symmetries play a central role in holographic computation of scattering amplitudes. We would ideally like to construct an explicit example of such a theory to provide a concrete proposal between a gravitational theory in asymptotically flat spacetimes and a Carroll CFT with additional symmetries living on its null boundary.…”
Section: Discussionmentioning
confidence: 99%
“…For example, the SL 2 current algebra at level zero turns out to be a symmetry algebra [20] of tree level graviton scattering amplitudes. In fact it has been shown that the w 1+∞ is a symmetry algebra [22][23][24][25]28] for massless scattering amplitudes. This also holds at the loop level in some special cases.…”
Section: The Central Claimmentioning
confidence: 99%
See 1 more Smart Citation
“…The numerical factor 3 2 in the first line of the first binomial coefficient is given by (2 + 3 2 ) (which is the sum of numerical numbers with minus sign in the numerator of previous weights) minus 2. The numerical factor 1 2 in the second line of the first binomial coefficient is given by 3 2 (which is the numerical number for the gravitino with minus sign in the numerator of previous weights) minus 1 10 . The first binomial coefficient above can be obtained from (3.15) by taking the shift l → (l + 1 2 ).…”
Section: The Ope Between the Graviton And The Gravitinomentioning
confidence: 99%
“…In [8], the supersymmetric w 1+∞ algebra has been identified with the corresponding soft current algebra in the supersymmetric Einstein-Yang-Mills theory. The relevant works on the celestial holography in the various directions can be found in [9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24,25,26,27,28,29,30,31,32,33,34,35]. See [1] for more complete literatures.…”
Section: Introductionmentioning
confidence: 99%